Odpowiedź :
Odpowiedź:
a)[tex]\left \{ {{3x-y=6} \atop {-3x+2y=12}} \right.[/tex]
-y=6-3x
y=3x-6
dodaję oba równania
y=18
3x-6=18
3x=24
x=8
(x,y)=(8,18)
b)[tex]\left \{ {{x+2y=12} \atop {-x+3y=3}} \right.[/tex]
x=12-2y
dodaję oba równania
5y=15
y=3
x=12-2*3=6
(x,y)=(6,3)
c)[tex]\left \{ {{-2x+3y=5/*3} \atop {3x-4y=1,5/*2}} \right. \\\left \{ {{-6x+9y=15} \atop {6x-8y=3}} \right.[/tex]
3y=5+2x
y=[tex]\frac{5+2x}{3}[/tex]
dodaję oba równania
y=18
[tex]\frac{5+2x}{3} =18/*3\\5+2x=54\\2x=49\\x=\frac{49}{2}[/tex]
(x,y)=([tex]\frac{49}{2}[/tex],18)